Kamimuria gressitti, a New Stonefly Species from China (Plecoptera: Perlidae), and New Records of K. atra from Vietnam - Stark, Bill P. (Illiesia, 2013)
A new species of Kamimuria, based on male and female specimens collected in 1948 by J.L. Gressitt and colleagues in Hubei Province, China, is described and compared to related species of the genus. New provincial records are also given for K. atra Sivec & Stark from Cao Bang and Nghe An, Vietnam.
Keywords: entomology; Perlidae; Plecoptera; Vietnam; Kamimuria; new species; new distributional records; China